Zonificación de riesgos por deslizamientos en el barrio San Vicente del cantón Sozoranga. - Chamba Pinta, Pedro Armando (2010)
Geological risks zoning becomes an instrument technicaian gestion, although a ordered land planning, must consider the conditions physics and mecachanicals of the soli and subsoil, these associates with the existents geological riks, mainly when the infrastructure work and activities economics partner could be affected by processes of movements in mass. The present proyect was developed gethering the information of the different geoambientales parameteres in the fiel work, the these data will be prosecuted in the oficce, with the help of the programs SIG: ForeSight, AutoCAD 2010, ArcView 3.2, ArcGis 9.2, like which we decided to use the empiric method, it consists in the analysis of eachone of the variables of the conditions factors for the ocurrence of landslide, such as: the geology, solopes, inventory of movements in mass, geomorphology, geomecanica, geotechics, covering of the vegetation and use the soil: these complemented with the unchain factors: precipitations and antropicas activities, allowing in this way, to relate and to interpret through the systematic crossing of the thematics maps the degree of severity of the menaces and it's posibles damages, finally abtaining the map of risk, in the which we can identify the different zones of vulnerability, these are distributed according to the conditions geomabientales of the place of study. The conclusions and recomendations are exposed in the respective chapter of this technician inform, these will serve of base so that the charged entities of the ordered land and risks gestion establish the svitable norms to preserve the security of the inhabitants, also the infrastructure that can be affected in the San Vicente neighbarhood of the Sozoranga canton, province of Loja